The Divine Council and Israelite Monotheism - McGinn, Andrew R. (My University, 2005)
The Old Testament contains a number of depictions of a divine councilor assembly of the gods in the heavens. Several of these scenes form episodic narratives that provide a window into the divine realm and insight into the workings of the heavenly court. The closest cultural and linguistic parallel to the biblical council is found in the Ugaritic texts from Ras Shamra. The parallel members in the Old Testament are seldom considered gods by scholars, in contrast to those in the pantheon in the Ugaritic literature. This thesis calls into question the validity of this distinction and proposes that in these episodic scenes these members are deities under the presidency of YHWH. Power in the heavens is consolidated in the council permitting a view of god that is pluralistic and yet unified. YHWH is its head and he sets its agenda, announces its decisions and commissions its agents.
Keywords: theology; old testament; biblical; Biblical Studies; Religious Thought, Theology and Philosophy of Religion; Biblical Studies